A New Dynamical Index for India-Burma Trough - Kui Liu; Jinlin Zha; Ruowen Yang; Jilong Chen (Advances in Meteorology)
Based on the vertical velocity field of reanalysis datasets, this study defines a new dynamical index for the India-Burma trough and supports this index’s advantages by analyzing reanalysis and observational datasets. For a convenient understanding, the vertical velocities of 5 levels ranging from 700 hPa to 500 hPa within the area of 15.625°N–24.375°N and 90.625°E–100.625°E are multiplied by −1 and summed up into a time series involving each year from 1979 to 2012. The standardized value of the time series is defined as the index of India-Burma trough (IIBT). IIBT can reflect the characteristics of the annual strength and the interdecadal variation of the India-Burma trough. IIBT can also well reveal the relationship between the India-Burma trough and its upstream teleconnection. What is more, through a correlation analysis on the grid point precipitation field, respectively, with the IIBT and the India-Burma trough indices defined with vorticity and geopotential height, over southern Asia the correlation pattern between the IIBT and the precipitation field is found to nearly be the sum of the correlation patterns of the latter 2 indices with the precipitation. To the south of the TP, the correlation field between the IIBT and the grid point precipitation shows dipolar distribution, which is consistent with the correlation patterns of the IIBT with the vertical velocity, specific humidity, and the mid-level geopotential height in the same spatial location. IIBT is beneficial for more accurate study of the impact of the India-Burma trough on the associated weather and climate.